Legal empowerment and group-based inequality - Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Legal empowerment has become widely accepted in development policy circles as an approach to addressing poverty and exclusion. At the same time, it has received relatively little attention from political scientists and sociologists working on overlapping and closely related topics. Research on legal empowerment has been largely applied, with its clearest grounding in the fields of law and economics. This is an introductory/framing paper for a collection of studies on legal empowerment and group-based inequality to be published in a special issue of the Journal of Development Studies. It provides a brief introduction to legal empowerment and advances two broad arguments. First, that an ethnic group-focused approach is a useful starting point in considering the impact of legal empowerment and other development interventions. Second, that the state, via the law, contributes to ethnic inequalities in four broad ways - via its written laws, via their implementation and actual practice, through historical legacies of law and practice, and through the ethnic hegemony embedded in the system. Thinking about legal empowerment initiatives within this framework provides understanding of both their potential and their limitations.
Keywords: K00; K4; D63; I30; D71; A12; 330; legal empowerment; ethnicity; horizontal inequality; inequality; exclusion; human rights